Discourse strategies and linguistic features of life insurance sales meetings - Ishak, Wan Irham (2017)
This study investigated the discourse of life insurance sales meeting, which has not received much attention from linguists, especially studies that utilise the discourse analysis approach. The aims of the study were to describe the structure of life insurance sales meeting and the use of discourse strategies and linguistic features in conducting this type of meeting. The data of the study consisted of transcribed discourse of insurance sales meetings. This study was guided by the theoretical approaches of including life insurance structure of buying and selling interaction (Taylor and Woodside, 1980), discourse strategies (Hayashi, 1991; Coulthard et al., 1992; Stenstrom, 1994; Holmes, 2000; Tannen, 2007; Edu-Buandoh and Ahieley, 2012), linguistic features (Leech and Short, 1984; Ler 2005) and code-switching (Poplack, 1980; Ariffin and Rafik-Galea, 2009; Nil and Paramasivam, 2012). The analysis of the data was conducted qualitatively and quantitatively to examine the stages of life insurance sales meetings, discourse strategies, linguistic features and code-switching performed in these meetings. The stages of life insurance sales meeting were derived from the interaction between insurance agents and their clients, which was based on the framework of analysis by Taylor and Woodside (1980). In this analysis, observable stages that emerged from speakers’ communication were discussed to explain the meeting stages. Evidence from the discourse revealed that the use of stages in the context of life insurance sales meeting was adhered to by most of the insurance agents. The findings also suggest that life insurance sales meeting stages depend largely on the individual agent and his or her client. The study concluded that the recorded life insurance sales meetings observed the five stages of sales meetings as proposed by Taylor and Woodside (1980). However, certain stages may recur depending on the ongoing interaction between the insurance agents and their clients. The data revealed that question, backchannel, repetition and small talk were the most prominent discourse strategies employed by the insurance agents in the sales meetings. The linguistic features, on the other hand, were mostly insurance related words and were quantitatively analysed based on the frequency counts of the lexical features. Lastly, implications for the study indicate that the actual meeting may be conducted differently to suit a particular prospect and context.